SEROEPIDEMIOLOGICAL SURVEY OF EQUINE INFECTIOUS ANEMIA IN RONDONIA STATE, BRAZIL - GUIRAUD, A. C. C.; BELO, M. A. A.; MORAES, A. C.; MANRIQUE, W. G.; SOUZA, L. M.; SILVA, I. C.; SOUZA, E. P. (Ars Veterinaria, 2017)
Based on the importance of equine infectious anemia (EIA), this study aimed to analyze the spatial distribution and report the occurrence rates of EIA through a seroepidemiological survey and evaluate the actions taken by the Agrosilvopastoral Defence Agency of the State of Rondônia (IDARON) from January 2014 to December 2015. There was a direct relationship between the human development index (HDI) and the number of horses in the different areas of the Rondonia. 7,729 properties were analyzed, in which 19,805 horses were examined, with a mean seropositivity for EIA of 1.15% in 2014 and 1.01% in 2015. Despite the low incidence of seropositive horses for the EIA virus, sanitary control procedures imposed by IDARON with the sacrifice of 95.97% of sick animals in 2014 and 90% in 2015 resulted in a decrease of 28.22% of positive animals between the years 2014 and 2015. Therefore, to achieve an effective reduction in the prevalence of this disease, all positive animals should be isolated and subsequently sacrificed, as they are disseminators of the disease. Many farmers, however, do not understand the real importance of the proliferation of EIA by the presence of carrier animals in the herds.